REPRESENTATIONAL COMPETENCE AND CONCEPTUAL UNDERSTANDING IN LINEAR MOTION: DIFFERENCES BY REPRESENTATION TYPE AND GENDER - Koswojo, Jane; Kusairi, Sentot; Sutopo, Sutopo; Herwinarso, Herwinarso; Rizkyanti, Elta; Daeng, Firza Farahdiba (Magister Scientiae, 2026)
This study investigates the correlation between representation competence and conceptual understanding of linear motion kinematics, by representation type and gender, among undergraduate students. A quantitative survey design was conducted with 228 students (136 male and 92 female) who had completed a basic physics course. Data were collected using seven validated essay items adapted from the Test of Understanding Graphics in Kinematics (TUG-K2) to measure students' representational competence and conceptual understanding across graphical, diagrammatic, and verbal representations. Descriptive statistics, Kruskal-Wallis test, Wilcoxon test, and Pearson correlation analysis were used. Results showed that students' representation competence was generally moderate (mean=1.130) and differed significantly across representation types, while their conceptual understanding was relatively low (mean=0.419) and varied significantly across kinematics concepts. Although female students showed slightly higher average representation competence scores, no statistically significant gender differences were found in either representation competence or conceptual understanding. A strong positive correlation was identified between representation competence and conceptual understanding, indicating a close association between the two constructs. However, the correlational design does not allow causal conclusions to be drawn. These findings highlight the importance of explicitly integrating various representations into physics teaching to support deeper conceptual understanding in linear motion kinematics